Clinical Practice Protocol for Management of Women of Childbearing-Age with Epilepsy - Ferro, Margarida (2023)
Women of childbearing-age with epilepsy presents with challenges in prevention, planning and orientation of gestation and post-partum. Gestation in women with epilepsy represents 0.3% to 0.5% of all pregnancies, and one third of women with epilepsy is in childbearing-age. Epilepsy may be associated with serious complications in pregnant women, with a higher risk of congenital malformations, intrauterine growth restriction and neurocognitive development disorders in children, due to adverse effects of antiseizure drugs (ASD). Women should be informed that the risk of fetal congenital malformations depends on the type, number, and dosage of ASD. The choice of drugs associated with a lower incidence of congenital malformations, as well as monitoring and adjusting its dosage are essential for an adequate seizure control. Choosing the treatment for women of childbearing-age should be based on an early and shared decision between patient and doctor, and when appropriate, shared with the patient’s legal representative as well. Discussions should include careful evaluation of the risk-benefit relationship of reasonable drugs for the type of seizures/epilepsy. Women of childbearing-age and pregnant women with epilepsy should also be informed of the low risk of seizures and complications during labor. Vaginal delivery should be considered, as epilepsy is not a formal indication for cesarian delivery. A careful follow-up in post-partum is also fundamental, in which is important to check dosages of ASD, reintroduce contraceptive methods and reassure that care has been taken to minimize the risk of maternal and newborn lesions due to seizures. Follow-up should be multidisciplinary, including the attending neurologist, obstetrician, and general physician. We present a clinical practice protocol that aims to guide multidisciplinary teams managing women of childbearing-age with epilepsy, regarding contraception, fertility, pregnancy and post-partum period.